Exploration of the Validity of the Moral Competency Inventory Instrument: Analysis of Validation Methods from Various Studies - Nurcahya, Fikri; Riyadi, Riyadi; Ridwan, Achmad (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
This study explores the validity of the Moral Competency Inventory (MCI) as a moral intelligence measurement instrument applied across cultural contexts. Based on a literature review of several studies, this study highlights the strengths, variations, and gaps in the validity of the MCI. The findings indicate that in general, the MCI has good validity in terms of internal structure and content, with four main dimensions of integrity, responsibility, compassion, and forgiveness being relatively stable across cultures. However, the adaptation of the MCI in different cultural contexts results in variations in the response process and the influence of demographic factors, such as age, gender, and cultural background. In addition, several studies show inconsistencies in the convergent and discriminant validity of the MCI, especially in relation to local instruments measuring morality. These gaps indicate the need for further research on the social impact of the use of the MCI across cultures. This study recommends cultural and linguistic adjustments in the future development of the MCI to improve the validity of this instrument as a universal moral intelligence measurement tool.